Effect Of Mime-Mirror Therapy on Facial Expression in Bell’s Palsy Patients - Kurian Varkey, Seby Anna; Bhodaji, Satyam (Journal of Neonatal Surgery, 2025)
Background: Acute facial nerve paralysis that impacts face symmetry, expressiveness, and function is known as Bell's palsy. Restoring facial movement and minimizing impairment are the goals of several therapeutic approaches. Using standardized outcome measures, this study assesses and contrasts the effects of mirror therapy, mime therapy, and mime-mirror therapy on face rehabilitation. Objective: to evaluate how individuals with Bell's palsy's facial function was affected by three distinct facial rehabilitation techniques: Mirror Therapy alone (Group C), Mime Therapy alone (Group B), and Mime-Mirror Therapy (Group A). Methods: Thirty patients were randomly assigned to three groups (ten each) in a randomized controlled experiment. The Facial Disability Index (FDI) and the Sunnybrook Facial Grading System (SB-FGS) were the outcome measures employed. Scores were taken before and after therapy, and statistical analyses such as ANOVA, paired t-tests, and effect size (Cohen's d) were used. Results: Following the intervention, all groups demonstrated statistically significant improvement (p < 0.05). However, the most notable improvement in both SB-FGS and FDI scores was shown by Group A (Mime-Mirror Therapy). Significant differences in results were found by between-group comparison, with Group A outperforming Groups B and C (p < 0.01). Group A had the greatest effect size, suggesting that the combination strategy had a significant therapeutic impact. Conclusion: For Bell's palsy patients, Mime-Mirror Therapy improves facial function more effectively than either Mime Therapy or Mirror Therapy alone. Neuromuscular recovery and patient-reported outcomes are improved when motor retraining and visual feedback are combined. It is advised to conduct more studies with bigger sample sizes and longer-term monitoring.